Morphological description of the pupa and fourth-instar larva and redescription of the adults of Psorophora (Psorophora) pallescens Edwards (Diptera: Culicidae) - Stein, Marina; Laurito, Magdalena; Rossi, Gustavo Carlos; Almirón, Walter Ricardo (Zootaxa, 2009)
The adult male and female of Psorophora (Psorophora) pallescens Edwards are redescribed. The pupa and fourth-instar larva are described for the first time. The male genitalia, pupa and fourth-instar larva are illustrated. Information on distribution, bionomics and taxonomy is also included. Psorophora pallescens adults differ from the other species of the subgenus in the coloration of the scutum and abdomen. The larva can be distinguished from Psorophora ciliata based on characters of the head, thorax and abdomen.